Augmented Reality-Based Navigation System for Wrist Arthroscopy: Feasibility - Zemirline, Ahmed; Agnus, Vincent; Soler, Luc; Mathoulin, Christophe L.; Liverneaux, Philippe A.; Obdeijn, Miryam (Journal of Wrist Surgery, 2013)
Purpose In video surgery, and more specifically in arthroscopy, one of the major problems is positioning the camera and instruments within the anatomic environment. The concept of computer-guided video surgery has already been used in ear, nose, and throat (ENT), gynecology, and even in hip arthroscopy. These systems, however, rely on optical or mechanical sensors, which turn out to be restricting and cumbersome. The aim of our study was to develop and evaluate the accuracy of a navigation system based on electromagnetic sensors in video surgery.Methods We used an electromagnetic localization device (Aurora, Northern Digital Inc., Ontario, Canada) to track the movements in space of both the camera and the instruments. We have developed a dedicated application in the Python language, using the VTK library for the graphic display and the OpenCV library for camera calibration.Results A prototype has been designed and evaluated for wrist arthroscopy. It allows display of the theoretical position of instruments onto the arthroscopic view with useful accuracy.Discussion The augmented reality view represents valuable assistance when surgeons want to position the arthroscope or locate their instruments. It makes the maneuver more intuitive, increases comfort, saves time, and enhances concentration.
Keywords: arthroscopy; augmented reality; computer-guided surgery; wrist